Quantifying the Role of Transition Metal Plating in the Cathodic Activation of Corroding Magnesium - Hamilton McMurray (ECS Transactions, 2017)
This paper examines the effect that transition metal ions have on the corrosion behaviour of high purity magnesium. A series of experiments indicate the ability of the selected transition metal ions to accelerate corrosion through cathodic (re)plating aiming to gain an insight on the Mg corrosion activation described in recent publications. High purity magnesium samples were used in conjunction with known additions of Fe2+, Cu2+, Zn2+ and Mn2+ cations. The results indicate that the presence of transition metal ions in the corrosive electrolyte leads to transition metal (re)plating and to an increase of the magnesium corrosion rate. By systematically varying the transition metal ion concentration it was possible to determine the relative efficiencies of the selected metal cations. It was also observed that the metal (re)plating process and the efficiency of the cathodic activation were limited by the formation of insoluble transition metal (hydr)oxide precipitates and the time-dependent hydrolysis.